Peritoneal Breach as an Indication for Exploratory Laparotomy in Penetrating Abdominal Stab Injury: Operative Findings in Haemodynamically Stable Patients - Jasmina Kevric; Victor Aguirre; Kate Martin; Dinesh Varma; Mark Fitzgerald; Charles Pilgrim (Emergency Medicine International)
Introduction. Management of haemodynamically stable patients with penetrating abdominal injuries varies from nonoperative to operative management. The aim was to investigate whether peritoneal breach when used as an indication for exploratory laparotomy appropriately identified patients with intra-abdominal visceral injury. Methods. We conducted retrospective cohort study of all patients presenting with PAI at a major trauma centre from January 2007 to December 2011. We measured the incidence of peritoneal breach and correlated this with intra-abdominal visceral injury diagnosed at surgery. Results. 252 patients were identified with PAI. Of the included patients, 71 were managed nonoperatively and 118 operatively. The operative diagnoses included nonperitoneal-breaching injuries, intraperitoneal penetration without organ damage, or intraperitoneal injury with organ damage. The presenting trauma CT scan was reported as normal in 63%, 34%, and 2% of these groups, respectively. The total negative laparotomy/laparoscopy rate for all patients presented with PAI was 21%, almost half of whom had a normal CT scan. Conclusion. We found that peritoneal breach on its own does not necessarily always equate to intra-abdominal visceral injury. Observation with sequential examination for PAI patients with a normal CT scan may be more important than exclusion of peritoneal breach via laparoscopy.